Myotonia and myotonic discharges of dystrophic myotonia type 1 at the first decade onset: a literature review and data of the case series - S. A. Kurbatov; V. M. Kenis; M. V. Savina; I. S. Kleimenova; N. S. Priymak; Yu. V. Kryukov; A. A. Kokorina; N. V. Ryadninskaya; I. A. Kuznetsova; O. A. Shchagina; A. V. Poliakov (Нервно-мышечные болезни, 2022)
Background. Dystrophic myotonia type 1 (DM1) is the most common muscular dystrophy in patients of any age. Myotonia “delayed relaxation of muscle” is the leading symptom in DM1 and can occur at any time after onset disease. Myotonia symptoms and electrical myotonia registration are delayed after onset in patients with congenital and infantile forms of DM1. This makes it difficult to diagnose and prevent fatal complications in these patients in a timely manner. Objective: presentation of the clinical data and results of needle electromyography in patients with DM1 onset in the first decade of the life; determination of the first symptoms of the disease, to estimate the age of myotonia and electrical myotonia manifestation for the optimization of the timely diagnostics of the disease.Materials and methods. 13 patients with DM1 aged from 2 months to 34 years were described. 10 patients underwent needle electromyography with analysis of spontaneous activity and needle EMG pattern. The diagnosis was made on the basis of clinical and paraclinical manifestations of the disease and identification of an increase in CTG repeats (>50) in the DMPK gene.Results. The onset with extramuscular signs of respiratory and/or feeding disturbances, dysarthria, school learning disorders, autism spectrum disturbance and “floppy infant syndrome” was noted as the first symptoms of the disease. Clinical myotonia symptoms and electrical manifestations of myotonia were absent in all patients for a long time after the disease onset. DM1 was confirmed in all mothers, however in 5 cases the onset of the disease was later than the first symptoms in patients with congenital and childhood onset forms of DM1.Conclusion. The first symptoms of the congenital and infantile forms of DM1 are not specific and occur in a wide range of diseases. Such discriminating signs of DM1 as clinical myotonia, distal muscle atrophy and electrical myotonia appear much later than the onset disease. In the group of patients before and after the formation of phrasal speech, the presented combinations of symptoms allow diagnostics of the congenital and infantile forms of DM1 at the onset of the disease. In its turn, it allows genetic counseling in burdened families and timely prevention of fatal complications.